2015
DOI: 10.4238/2015.april.10.22
|View full text |Cite
|
Sign up to set email alerts
|

Association between the CYP11B2 gene ˗344T>C polymorphism and coronary artery disease: a meta-analysis

et al.

Abstract: ABSTRACT. Numerous studies have evaluated the association between the CYP11B2 gene ˗344T>C polymorphism and coronary artery disease (CAD) risk. However, the specific association is still controversial. To address this issue, PubMed, EMBASE, and China National Knowledge Infrastructure databases were searched for eligible articles that reported on the relationship between the CYP11B2 gene ˗344T>C polymorphism and CAD, and were published before April 2014. Data from five separate studies with 3687 subjects were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Many studies have shown a correlation between À344C/T and MACEs in different ethnicities. 22 The polymorphism was positively correlated with left ventricular mass and thickness in EH; 23,24 left ventricular hypertrophy is an important predictor of cardiovascular morbidity and mortality in patients with hypertension. 25 In a metaanalysis, Yin et al indicated that À344C/ T polymorphism might be associated with CAD in Caucasian and Asian populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Many studies have shown a correlation between À344C/T and MACEs in different ethnicities. 22 The polymorphism was positively correlated with left ventricular mass and thickness in EH; 23,24 left ventricular hypertrophy is an important predictor of cardiovascular morbidity and mortality in patients with hypertension. 25 In a metaanalysis, Yin et al indicated that À344C/ T polymorphism might be associated with CAD in Caucasian and Asian populations.…”
Section: Discussionmentioning
confidence: 95%
“… 5 In an in vitro study, the −344C/T polymorphism in the CYP11B2 promoters was shown to affect binding of the SF-1 transcription factor and thus might influence gene expression; binding was 4 times stronger with the C allele than with the T allele. 21 Two studies 22 , 23 indicated that increased aldosterone production was associated with the C allele. Our results also demonstrated that presence of the C allele increased the risk of MACE in this Chinese EH population.…”
Section: Discussionmentioning
confidence: 99%
“…However, an association of the -344 genotype with aldosterone levels has been inconsistent, with several studies reporting an association between the -344T allele and higher levels 15 , 27 . Moreover, a meta-analysis suggested that the -344T>C polymorphism in the C YP11B2 gene might be associated with susceptibility to CAD in Caucasians and Asians 28 . However without stratification by the gender, Mishra et al reported that CYP11B2 was not associated with either CAD or left ventricular dysfunction in an Indian population 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study on 201 CAD patients and 201 controls form Italian population have detected that CYP11B2 polymorphism and CC genotype were associated with CAD risk in crude analysis with borderline significance which is lost by stratification to the confounding factors as smoking and family history [82]. A meta-analysis suggested that the −344T>C polymorphism in the CYP11B2 gene might be associated with susceptibility to CAD in Caucasians and Asians [83]. A study on 609 Taiwanese male and female subjects who were unrelated and received coronary catheterization found that the C/C allele occurred more frequently in females who had CAD, and that it was associated with higher left ventricular mass (LVM) and left ventricular end diastolic diameter (LVEDD) [84].…”
Section: Cyp11b2 Genotypic Variants and Coronary Artery Diseasementioning
confidence: 98%
“…The underlying mechanism by which the CYP11B2 ˗344T>C polymorphism can increase the risk for CAD remains unclear. However, it is related to its effect on increasing expression of CYP11B2, thereby increasing aldosterone secretion [83]. Also, the influence of gene-environment interaction has been involved as an etiological factor for CAD risk.…”
Section: Cyp11b2 Genotypic Variants and Coronary Artery Diseasementioning
confidence: 99%